Eine mehrdimensionale Untersuchung der Emotionsregulation im Kontext Nicht-Suizidaler Selbstverletzung im Jugendalter - Sigrist, Christine; Resch, Franz; Kaess, Michael; Koenig, Julian (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2021)
ZUSAMMENFASSUNG - - The ability to regulate one’s emotions (emotion regulation, ER) with regard to individual short- and long-term goals presents one of the most central human skills. A disrupted development of ER skills is associated with psychopathological outcomes. Non-suicidal self-injury (NSSI) presents a frequent and impairing phenomenon among young individuals. Disruptions regarding various aspects of ER are involved in the development and maintenance of NSSI. In the present study, we examined ER from a multidimensional perspective, including a sample of female adolescents meeting DSM-5 criteria for NSSI disorder (N = 30) and a psychologically healthy control group (N = 30). In line with results from previous studies, female adolescents with NSSI exhibited considerable difficulties regarding all aspects of ER investigated. Furthermore, various aspects of ER were distinctly linked with depressive and BPD symptomatology. Differences in NSSI frequency between participants largely went back to difficulties regarding specific aspects of ER, in combination with the self-rated severity of exposure to early life maltreatment. With regard to clinical practice, the use of interventions to improve particular aspects of ER, under simultaneous consideration of the individual developmental history and psychopathological impairment, might provide an efficient approach to mediate long-lasting change in the treatment of deliberate self-harm.